Pressure-dyeing machine in use at Althouse Customer Service Laboratory (1960)
View of Warren Crowther removing a skein, a length of yarn wound in a loose coil, from the cylinder of a pressure-dyeing machine used for the application of colored dyes. This photograph was taken at the Althouse Chemical Company Customer Service and Quality Control Laboratory in Reading, Pennsylvania. Based in Reading, Pennsylvania, the Althouse Chemical Company was founded in 1915 by C. Scott Althouse (1880-1970) as a small, family-owned firm specializing in fabric dyes of a superior quality and class. In 1954, the Crompton & Knowles Corporation of Worcester, Massachusetts acquired Althouse, which continued to operate as a division of Crompton & Knowles and a leader in the specialty dyes industry.
Keywords: Dye industry; Scientific apparatus and instruments; Dyes and dyeing; Althouse Chemical Company; Research, Industrial--Laboratories